Making Sense of Intransitivity, Incompleteness and Discontinuity of Preferences - Nurmi, Hannu (Cham, Heidelberg, New York, Dordrecht, London, 2022)
The starting point of modern social choice theory is the assumption that the individuals are endowed with complete and transitive preferences over the set of alternatives. Over the past 60 years a steady flow of experimental results has suggested that people tend to deviate from principles of choice stemming from the utility maximization theory. Especially in choices under risk, this behaviour makes intuitive sense. The usual culprit, i.e. the source of this "deviant" behaviour, is most often found in the violation of transitivity or - under risk - of the monotonicity in prizes principle. We show that there are grounds for arguing that even the completeness principle as well as continuity of preferences may, quite plausibly, be violated.
Group Decision and Negotiation: A Process-Oriented View